2021
DOI: 10.3390/ai2010008
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Multilayer Perceptron, Radial Basis Function Artificial Neural Networks and Machine Learning Image Segmentation for the Dimension Reduction and the Prognosis Assessment of Diffuse Large B-Cell Lymphoma

Abstract: The prognosis of diffuse large B-cell lymphoma (DLBCL) is heterogeneous. Therefore, we aimed to highlight predictive biomarkers. First, artificial intelligence was applied into a discovery series of gene expression of 414 patients (GSE10846). A dimension reduction algorithm aimed to correlate with the overall survival and other clinicopathological variables; and included a combination of Multilayer Perceptron (MLP) and Radial Basis Function (RBF) artificial neural networks, gene-set enrichment analysis (GSEA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 25 publications
1
55
0
Order By: Relevance
“…Finally, high expression of PD-L1 was associated with poor prognosis in DLBCL [44]. This result was also recently confirmed by our group [45], but, in this research, the CSF1R did not correlate with the PD-L1 expression. Another marker that we have recently described is the apoptosis inhibitor TNFAIP8, which is associated with a poor prognosis of the patients [28].…”
Section: Discussionsupporting
confidence: 84%
“…Finally, high expression of PD-L1 was associated with poor prognosis in DLBCL [44]. This result was also recently confirmed by our group [45], but, in this research, the CSF1R did not correlate with the PD-L1 expression. Another marker that we have recently described is the apoptosis inhibitor TNFAIP8, which is associated with a poor prognosis of the patients [28].…”
Section: Discussionsupporting
confidence: 84%
“…The analysis was performed to predict all subtypes simultaneously and then each subtype against the others. The multilayer perceptron was performed as we have recently described [17,[19][20][21][22][23].…”
Section: Multilayer Perceptron Analysismentioning
confidence: 99%
“…Another inhibitor, the Survivin, was also found overexpressed in DLBCL [47] and in ABC molecular type DLBCL the overexpression was also associated to a poor prognosis [47]. Besides, we recently described that high expression of another apoptosis inhibitor (TNFAIP8) was associated with a poor prognosis of DLBCL [40]. In this project the protein expression of Caspase-8 was analyzed in a series of Tokai University's, and we found that high expression was associated with a favorable survival of the patients.…”
Section: Discussionmentioning
confidence: 94%
“…Several software were used in this research according to the manufacturer's instructions: R software for statistical computing version 3.6. 2a-d) and Radial Basis Function analysis using the immunohistochemical data was performed following the manufacturer's instructions, and as we have thoroughly described in our previous publications [39,40]. In this neural network analysis, the prediction of Caspase-8 by the other related markers of the pathway was performed using the immunohistochemical data of Caspase-8 as a dichotomic variable (high vs. low, with the same cut-off of the overall survival).…”
Section: Software and Artificial Neural Network Analysismentioning
confidence: 99%